PEMBERDAYAAN MASYARAKAT DALAM PENGAWASAN PELAYANAN PUBLIK DAN PENCEGAHAN MALADMINISTRASI DI DESA TELAGA MURNI - Riskyani, Siska Kartikasari; Irham, Irham; Chairunnisa, Nurlaila Maysaroh (DEVOSI, 2022)
In providing public services to the community there are still many maladministrations, such as protracted delays, demand for rewards, discrimination, incompetence, not providing services, conflicts of interest, and others.Based on this, not a few of the people choose a quick way to get public services in the village.Therefore, it is important to educate the community and village apparatus related to supervision of public services and prevention of maladministration in the village environment, so that the implementation of public services in accordance with Law No. 25 of 2009. The implementation method used is with blended system seminars, through face-to-face meetings and through zoom meetings.The targets in this activity are the Village Consultative Agency (BPD) as a representation of the village community, and the Telaga Murni Village Apparatus.It is expected that in this activity the community knows better how the public service is carried out and can report if there is an allegation of maladministration, and it is also expected that this activity can provide a better understanding of the village apparatus in minimizing maladministration in public services in the village.